Unlocking the Power of Agile Methodology: A Journey to Developing Software and Web Applications - Ballamudi, Venkata Koteswara Rao (Engineering International, 2022)
Agile development approaches are becoming increasingly significant in the current circumstances. Throughout the past few years, there has been a rise in the number of software application development projects that use agile approaches. It is a new paradigm of research that crosses disciplinary boundaries. This article delves into the iterative and collaborative approach of Agile, highlighting its ability to enhance project flexibility, customer satisfaction, and product quality. It showcases real-world examples of Agile implementation and shares best practices for successful adoption. The study covers Agile’s introduction, adoption, usage, and analysis in both engineering streams. The remaining portion of the article provides an overview of the critical distinctions between applying agile methodologies to software engineering and web engineering. It explains the constraints inherent in using agile software and web engineering methodologies. Readers will gain insights into harnessing the agility of this methodology to adapt to changing requirements, reduce development risks, and deliver cutting-edge software solutions efficiently. Embrace Agile and embark on a journey toward software development excellence.